Analysis, structural characterization, and bioactivity of oligosaccharides derived from lactose. Issue 11 (21st January 2014) - Moreno, F. Javier; Montilla, Antonia; Villamiel, Mar; Corzo, Nieves; Olano, Agustín; Cifuentes, Alejandro
<x xml:space="preserve">Abstract</x> The increasing interest for prebiotic carbohydrates as functional food ingredients has promoted the synthesis of galactooligosaccharides and new lactose derivatives. This review provides a comprehensive overview on the chromatographic analysis, structural characterization, and bioactivity studies of lactose‐derived oligosaccharides. The most common chromatographic techniques used for the separation and structural characterization of this type of oligosaccharides, including GC and HPLC in different operational modes, coupled to various detectors are discussed. Insights on oligosaccharide MS fragmentation patterns, using different ionization sources and mass analyzers, as well as data on structural analysis by NMR spectroscopy are also described. Finally, this article deals with the bioactive effects of galacto oligosaccharides and oligosaccharides derived from lactulose on the gastrointestinal and immune systems, which support their consumption to provide significant health benefits.